Things Don't Really Exist Until You Give Them a Name: Unpacking Urban Heritage (TU Delft OPEN Publishing, 2023)
Urban heritage conundrumUrban built environments are spatial and material archives. Streets, buildings, open spaces, or infrastructures are registers of historical negotiations and repositories of data. Stories of power, geopolitics, economic systems, labour and culture can be revealed through road names and construction materials, portals and pediments, park benches and chimneys. Embodying our desires, needs, and resources, they condition how we live and interact with each other, and trigger countless reinterpretations and re-appropriations. Most of this dense layering is not immediately legible; it has not been decoded. Rather it is part of a more intuitive, lived sense of “urbanity” that generates contemporary individual and collective senses of identity and belonging. These complex urban palimpsests form the constitutive stages upon, with and against which everyday and extraordinary cultural life is performed.